2020
DOI: 10.1590/0074-02760200218
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal population dynamics of the primary yellow fever vector Haemagogus leucocelaenus (Dyar & Shannon) (Diptera: Culicidae) is mainly influenced by temperature in the Atlantic Forest, southeast Brazil

Abstract: BACKGROUND Southeast Brazil has recently experienced a Yellow Fever virus (YFV) outbreak where the mosquito Haemagogus leucocelaenus was a primary vector. Climatic factors influence the abundance of mosquito vectors and arbovirus transmission. OBJECTIVES We aimed at describing the population dynamics of Hg. leucocelaenus in a county touched by the recent YFV outbreak. METHODS Fortnightly egg collections with ovitraps were performed from November 2012 to February 2017 in a forest in Nova Iguaçu, Rio de Janeiro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
1
21
0
1
Order By: Relevance
“…leucocelaenus and possibly of Hg. janthinomys during dry season in the forest fragments was observed [163,225]; and a long-term study revealed that YFV persisted in the same forest area (in the interface environment) for at least 3 years consecutively [226].…”
Section: Sufficient Populations Of Infected Vectors and Year-long Activity Of Vectorsmentioning
confidence: 97%
“…leucocelaenus and possibly of Hg. janthinomys during dry season in the forest fragments was observed [163,225]; and a long-term study revealed that YFV persisted in the same forest area (in the interface environment) for at least 3 years consecutively [226].…”
Section: Sufficient Populations Of Infected Vectors and Year-long Activity Of Vectorsmentioning
confidence: 97%
“…The sampling locations are shown in (Fig 1). The state of Rio de Janeiro is characterized by having a hot and rainy climate between November and April (rainy period) and a cold and dry climate between May and October (dry period) [20].…”
Section: Study Areamentioning
confidence: 99%
“…However, the other vector species were not statistically significantly influenced by the climatic variables tested. Haemagogus leucocelaenus fluctuates in number of individuals throughout the year; however, the uninterrupted observation of eggs from this species in breeding sites illustrates that it maintains hematophagy activity throughout the studied months, regardless of climatic conditions 9 , 38 . This pattern of monthly egg collection and constant activity of Hg.…”
Section: Discussionmentioning
confidence: 87%
“…Weather conditions can also play a role in the vertical selection of oviposition sites 16 . Some studies have been shown that higher average temperatures favor mosquito eggs hatching, accelerates larval development 33,37 , and consequently speeds the YFV transmission 38 . Higher average temperatures also increase the frequency of biting activities 33 and reduce the duration of YFV incubation in the vector, which is the time elapsed between the mosquito's infectious blood meal and the arrival of these viral particles in its salivary glands 39,40 .…”
Section: Discussionmentioning
confidence: 99%